Javier Milei’s Argentina: What Lies Beneath His View on Higher Education? - Rabossi, Marcelo (International Higher Education, 2024)
The arrival of Javier Milei, an admirer of libertarian theorists such as Murray Rothbard or Friedrich Hayek, to the presidency of Argentina raises endless questions. For example, whether his almost exclusively economistic free-market views will be able to provide answers to the current educational crisis, with four out of 10 university entrants dropping out during the first year. Likewise, will his privatizing vision affect the public financing of the scientific system and national universities?